Predicting changes in aquatic toxicity of chemicals resulting from solvent or dispersant use as vehicle. (July 2016) - Kikuchi, Mikio; Nakagawa, Masamitsu; Tone, Suguru; Saito, Hotaka; Niino, Tatsuhiro; Nagasawa, Natsumi; Sawai, Jun
Abstract: The influence of two vehicles ( N, N -dimethylformamide [DMF] as solvent and polyoxyethylene hydrogenated castor oil [HCO-40] as a dispersant) on the acute toxicity of eight hydrophobic chemicals with a non-specific mode of action to Daphnia magna was investigated according to the OECD Guidelines for the Testing of Chemicals, No. 202. An increased 48-h EC50 value for D. magna or reduced toxicity resulting from the addition of HCO-40 to the test medium was observed for five of the eight chemicals examined. Each of eight chemicals was dissolved in water at a concentration of either 10 mg/L or 1.0 mg/L, with or without DMF or HCO-40. Silicone film as a model of a biological membrane was then immersed in each solution, and the concentration of each chemical in the water was monitored until equilibrium was reached for each test substance, after which the adsorbed amount of each chemical was determined. The amounts of p -pentylphenol and four other substances with log P ow (1-octanol/water partition coefficient) values greater than 3.4 adsorbed onto the silicone film decreased with increasing concentrations of HCO-40. However, 3-chloro-4-fluoronitrobenzene and two other substances with log P ow values less than 2.6 demonstrated no changes in adsorption with either increasing HCO-40 concentration or the addition of DMF. The reduced adsorption in the presence of a vehicle on the silicone film correlated closely with changes in toxicity. These results indicate that the methodology developed in this study enables the prediction of changes in toxicity resulting from the addition of vehicles to a test system. Highlights: The changes were studied on chemicals with a non-specific mode of action. Use of DMF or HCO-40 at 20 mg/L does not affect on the toxicity. 100 mg/L of HCO-40 may alter the toxicity of chemicals of high log P ow values. The adsorption changes by HCO-40 was closely correlated with the changes in toxicity. The adsorption test can predict toxicity changes by using vehicle.